Faktor-faktor yang Mempengaruhi Kebijakan Hutang - Masril Masril; Jefriyanto Jefriyanto; Yusridawati Yusridawati (Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to analyze the effect of company growth, asset structure, and liquidity on the company's debt policy. The population in this study are all food and beverage companies that are consistently listed on the IDX during the period 2017 – 2019. The sample was selected by purposive sampling with a total of 18 companies. This study uses secondary data in the form of annual financial report data and company annual reports for 3 years (2017-2019). The analysis technique used is descriptive statistical analysis and multiple regression analysis. The results of the study show that liquidity has a significant dan negative effect on the company's debt policy. Simultaneously company's growth, asset structure, and liquidity have a significant effect on the company's debt policy.